PAW patrol. Rubble on the double [videorecording (DVD)] - Bastien, Charles E.; Whitney, Jamie (Nickelodeon : Paramount Home Entertainment, 2021)
Get ready to raise the woof with Rubble and the rest of the PAW Patrol in these nine construction missions! Whether they₂re saving animals, superheroes, or even a rock-and-roll show, the pups can always build a plan to save the day!